Influence of grain size and composition, topology and excess free volume on the deformation behavior of Cu–Zr nanoglasses - Şopu, Daniel; Albe, Karsten (Beilstein Journal of Nanotechnology, 2015)
The influence of grain size and composition on the mechanical properties of Cu–Zr nanoglasses (NGs) is investigated by molecular dynamics simulations using two model glasses of different alloy composition, namely Cu64Zr36 (Cu-rich) and Cu36Zr64 (Zr-rich). When the grain size is increased, or the fraction of interfaces in these NGs is decreased, we find a transition from a homogeneous to an inhomogeneous plastic deformation, because the softer interfaces are promoting the formation shear transformation zones. In case of the Cu-rich system, shear localization at the interfaces is most pronounced, since both the topological order and free volume content of the interfaces are very different from the bulk phase. After thermal treatment the redistribution of free volume leads to a more homogenous deformation behavior. The deformation behavior of the softer Zr-rich nanoglass, in contrast, is only weakly affected by the presence of glass–glass interfaces, since the interfaces don’t show topological disorder. Our results provide clear evidence that the mechanical properties of metallic NGs can be systematically tuned by controlling the size and the chemical composition of the glassy nanograins.
Keywords: enhanced plasticity; metallic glasses; nanoglasses; shear bands

(untitled) - Gleiter, H. (Beilstein J. Nanotechnol., 2013)

(untitled) - Jing, J.; Krämer, A.; Birringer, R.; Gleiter, H.; Gonser, U. (J. Non-Cryst. Solids, 1989)

(untitled) - Weissmüller, J.; Birringer, R.; Gleiter, H. (Key Eng. Mater., 1993)

Proceedings of the 7th National Conference on the Physics of Non-Crystalline Solids - Weissmüller, J.; Schubert, P.; Franz, H.; Birringer, R.; Gleiter, H. (Cambridge, England, 4.8.1991-9.8.1991)

(untitled) - Ghafari, M.; Hahn, H.; Gleiter, H.; Sakurai, Y.; Itou, M.; Kamali, S. (Appl. Phys. Lett., 2012)

(untitled) - Witte, R.; Feng, T.; Fang, J. X.; Fischer, A.; Ghafari, M.; Kruk, R.; Brand, R. A.; Wang, D.; Hahn, H.; Gleiter, H. (Appl. Phys. Lett., 2013)

(untitled) - Chen, N.; Frank, R.; Asao, N.; Louzguine-Luzgin, D. V.; Sharma, P.; Wang, J. Q.; Xie, G.; Ishikawa, Y.; Hatakeyama, N.; Lin, Y. C.; Esashi, M.; Yamamoto, Y.; et al. (Acta Mater., 2011)

(untitled) - Fang, J. X.; Vainio, U.; Puff, W.; Würschum, R.; Wang, X. L.; Wang, D.; Ghafari, M.; Jiang, F.; Sun, J.; Hahn, H.; Gleiter, H. (Nano Lett., 2012)

(untitled) - Sopu, D.; Albe, K.; Ritter, Y.; Gleiter, H. (Appl. Phys. Lett., 2009)

(untitled) - Ritter, Y.; Şopu, D.; Gleiter, H.; Albe, K. (Acta Mater., 2011)

(untitled) - Şopu, D.; Ritter, Y.; Gleiter, H.; Albe, K. (Phys. Rev. B, 2011)

(untitled) - Albe, K.; Ritter, Y.; Şopu, D. (Mech. Mater., 2013)

(untitled) - Adibi, S.; Sha, Z.-D.; Branicio, P. S.; Joshi, S. P.; Liu, Z.-S.; Zhang, Y.-W. (Appl. Phys. Lett., 2013)

(untitled) - Franke, O.; Leisen, D.; Gleiter, H.; Hahn, H. (J. Mater. Res., 2014)

(untitled) - Adibi, S.; Branicio, P. S.; Zhang, Y.-W.; Joshi, S. P. (J. Appl. Phys., 2014)

(untitled) - Ritter, Y.; Albe, K. (J. Appl. Phys., 2012)

(untitled) - Plimpton, S. (J. Comput. Phys., 1995)

(untitled) - Mendelev, M. I.; Sordelet, D. J.; Kramer, M. J. (J. Appl. Phys., 2007)

(untitled) - Voronoi, G. (J. Reine Angew. Math., 1908)

(untitled) - Lee, J.-C.; Park, K.-W.; Kim, K.-H.; Fleury, E.; Lee, B.-J.; Wakeda, M.; Shibutani, Y. (J. Mater. Res., 2007)

(untitled) - Cheng, Y. Q.; Cao, A. J.; Sheng, H. W.; Ma, E. (Acta Mater., 2008)

(untitled) - Shimizu, F.; Ogata, S.; Li, J. (Mater. Trans., 2007)

(untitled) - Stukowski, A. (Modelling Simul. Mater. Sci. Eng., 2010)

(untitled) - Cheng, Y. Q.; Cao, A. J.; Ma, E. (Acta Mater., 2009)

(untitled) - Xiao, Q.; Sheng, H. W.; Shi, Y. (MRS Commun., 2012)

(untitled) - Sheng, H. W.; Luo, W. K.; Alamgir, F. M.; Bai, J. M.; Ma, E. (Nature, 2006)

(untitled) - Lee, M.; Lee, C.-M.; Lee, K.-R.; Ma, E.; Lee, J.-C. (Acta Mater., 2011)